Imprensa alternativa e contracultura: o jornal brasileiro Rolling Stone de 1972 - Ribas, Ana Helena Fabbro Dias [UNESP] (2012)
The present monograph is a historical research of one of the brazilian newspapers in a journalistic heterogeneous effervescence, referring to the proliferation of vehicles on alternative libertarians of the 60/70. The project gives visibility to the Rolling Stone newspaper as the document that disproved their own relevancy in the viability of the music production and counterculture inspired by North America, developing the repercussion of the new behavior of young flower power in the country. The personality of those who were in the journalistic team, the production schema, editorial and proposed tariffs would be in total congruency with the countercultural movement